Pentingnya Human Relations dalam Kegiatan Kehumasan - Imron Rosyidi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
The core point of human relations has been hospility, respect, emphaty and honesty. Human relations may be implemented as a wide range of human interactions including business, government, school and other social institutions. Human relation has been a way by which a manager encourage staffs to work together with such productive maneuvers to produce a symbiotic complementary. This approach is necessary for a manager in an attempt to orient staffs in achieving corporate goals. This will certeaintly lead to overall success of both individuals and corporate.